An exploratory study on shared value and its influence on brand image - Jackson, Amber-Lee (The IIE, 2018)
Societal issues, distrusting consumers and the trend towards meaningful brand building are all prevailing variables necessitating the demand for brands to engage in societal value creation to remain relevant (Enslin & De Beer, 2015; Porter & Kramer, 2011). Hence, this research explored the influence of shared value on Vintage Coffee’s brand image, a niche coffee shop operating in Pretoria, South Africa. Research was conducted using the interpretivist paradigm and made use of an exploratory research design. Standardised semi-structured in-depth interviews were used as they allowed the researcher to understand participant’s subjective perspectives regarding Vintage Coffee’s pursuit of shared value (Nieuwenhuis, 2016c). Interviews were conducted in the Vintage Coffee Menlyn branch whereby qualitative data was collected from six Vintage Coffee customers and was analysed using thematic analysis enabling the exploration of both covert and overt themes embedded in transcripts (Schreier, 2014). Findings indicated that Vintage Coffee’s pursuit of shared value positively influenced brand image by cultivating trust, nurturing a willingness to support and developing brand loyalty among participants. Therefore, this research contributes to assisting the brand manager with new evidence to support the allocation of resources and effort towards the preservation of Vintage Coffee’s shared value strategy as it effectively contributes towards influencing customer perceptions (brand image) pertaining to the brand (Marzocchi et al., 2013).
Keywords: Brand building; Brands; Brand image; Brand loyalty